Economics of Distributed Storage Systems : an economic analysis of arbitrage-maximizing storage systems at the end consumer level - Ahlert, Klaus-Henning (KIT Scientific Publishing, 2010)
Increasing the shares of Renewable Energy Sources (RES) and Distributed Energy Resources (DER) is one of the most important levers in many countries to cope with the environmental, political, and economic challenges of future energy supply. The underlying research question of this thesis is whether Distributed Storage Systems (DSS) at the end consumer level can economically foster the integration of intermittent and non-dispatchable resources by providing demand-side flexibility.